(untitled) (Cultura Económica, 2019)
Aberlardo Pithod describes in his article, as a native of the area, the interaction between culture and environment in the province of Mendoza. The author explains the geographical and climatic conditions that have always affected the territory of Mendoza. The unwelcoming space and the hostile weather are the defining characteristics. In this situation, the impressive development and the whole history of Mendoza show the strong will of its inhabitants, who have been able to overcome the difficulties of the weather, turning this territory into the prosperous region that we know today.